Annual dynamics of soil gross nitrogen turnover and nitrous oxide emissions in an alpine shrub meadow. (November 2019) - Hu, Xiaoxia; Liu, Chunyan; Zheng, Xunhua; Dannenmann, Michael; Butterbach-Bahl, Klaus; Yao, Zhisheng; Zhang, Wei; Wang, Rui; Cao, Guangmin
Abstract: Soil nitrogen (N) transformations play a vital role in maintaining grassland productivity and influence nitrous oxide (N2 O) emissions. To evaluate annual dynamics of soil gross N turnover and its effects on N2 O emissions in typical grasslands, we conducted year-round measurements of soil gross N turnover rates, inorganic N pool sizes and N2 O fluxes in an alpine shrub meadow of the Qinghai–Tibet Plateau. Gross ammonium (NH4 + ) and nitrate (NO3 − ) immobilization rates were calculated by the "isotope dilution method" (i.e., based on the consumption rates) and the "reformed difference method" (i.e., based on the differences between gross and net turnover rates). The "reformed difference method" avoids additional measurements of net N turnover rates in unlabeled soils compared to the traditional "difference method", and provides more reliable estimates of NH4 + immobilization in soils with low ambient NH4 + pool sizes than the "isotope dilution method". The annual gross rates of mineralization, nitrification, NH4 + and NO3 − immobilization amounted to 606 ± 43, 236 ± 27, 389 ± 24 and 82 ± 19 mg N kg −1 dry soil yr −1, respectively, in a topsoil of 10 cm. The soil gross N turnover rates during freezing and freeze–thaw periods contributed considerably to the annual totals (22–44%). Thus, the freezing and freeze–thaw periods were not dormant seasons for microbial N transformations, even under a frigid alpine climate. The annual N2 O emission was 0.20 ± 0.03 kg N ha −1  yr −1, 35% of which originated from a short-lived emission pulse during the freeze–thaw period (52 d). The promotion of gross mineralization increased soil NH4 + pool sizes, whereas the increase in gross nitrification did not enhance soil NO3 − pool sizes during the freeze–thaw period. Coupled nitrification–denitrification dominated NO3 − consumption and freeze–thaw related N2 O production and hence, the low NO3 − pool sizes were not indicative of the potential of pulsed N2 O emissions. Year-round measurements with intensive observations during both the non-freezing and freeze–thaw periods are indispensable to fully understand soil N cycling and its response to climate change in alpine ecosystems. Highlights: Annual gross N turnover and N2 O emissions were measured in an alpine meadow soil. An alternative method was used to estimate gross microbial ammonium immobilization. Microbial N turnover was persistent in frozen soils despite frigid alpine climate. Coupled nitrification–denitrification dominated freeze–thaw induced N2 O emissions. Year-round measurements are indispensable to fully understand soil N cycling.